Violence Towards Dentists A Survey Questionnaire - Karadayı, Beytullah; Varlık, Ende; Çakı, İbrahim Eray; Altınok, Mehmet; Kaya, Ahsen; Afşin, Hüseyin; Özaslan, Abdi (The Bulletin of Legal Medicine, 2016)
Objective: This study is aimed to determine the characteristics of the violence that dentists, who work at oral and dental health diagnosis and treatment centers, are exposed to and witness. The study also investigates the process that occurs after the incident.Materials and Method: A survey was conducted between July 1st and December 31st of 2014 among dentists who work at dental healthcare centers and faculties of dentistry in Istanbul. The survey consists of 3 sections. The sections are structured as followed: Section I, demographical information; Section II, the reasons and possible precautions; Section III, characteristics of the violence.Results: 48.5% (n=32) of the participants claimed that they were exposed to some kind of violence at least once in their professional lives. 65.6% (n=21) of them were exposed to a violent act in the past year. 71.9% (n=23) of these exposures were only verbal and 18.7% (n=6) included both verbal and physical violence. 95.5% (n=63) of the participants stated that there was a general increase in violent acts in society and 69.7% (n=46) stated that violent incidents increased in the work place. The study also showed that 86.4% (n=57) of the participants thought that the violence could have been prevented. Conclusion: Even though this study reflects the opinions of a small group, it shows that dentists are affected by the violence in the healthcare field.Keywords: Physical violence; Verbal violence; Violence
Keywords: physical violence; verbal violence; violence